A Nonbenzenoid 3D Nanographene Containing 5/6/7/8-Membered Rings - Liu, Pengcai; Lv, Hao-Han; Xue, Rui; Tang, Xiao-Yu; Chen, Xing-Yu; Qi, Liping; Wang, Xiao-Ye (Organic Materials, 2024)
Nanographenes (NGs) have attracted continuous attention in recent years owing to their opened bandgaps and optoelectronic applications. Especially, nonbenzenoid NGs containing non-six-membered rings have been developed rapidly due to their unique structures and properties. In this work, we employ nonbenzenoid acepleiadylene (APD) and the cyclooctatetraene (COT) moiety to construct the first three-dimensional (3D) NG containing 5/6/7/8-membered rings in one molecule (COT-APD). The calculated results prove that COT-APD has a saddle-like configuration similar to that of other COT-type molecules. Each APD segment in COT-APD keeps the inherent aromaticity of the APD moiety. Compared with other COT-type molecules, COT-APD shows a narrower bandgap, which indicates the superiority of APD in bandgap regulation. Furthermore, four reversible reductive waves are observed in electrochemical characterizations, demonstrating the excellent electron-accepting capability of COT-APD.
Keywords: nanographenes; nonbenzenoid arenes; cyclooctatetraene; acepleiadylene